The Efficiency of Hydroxychloroquine for the Treatment of Primary Sjögren’s Syndrome: A Systematic Review and Meta-Analysis - Wang, Xuan; Zhang, Tongyangzi; Guo, Zizhen; Pu, Jincheng; Riaz, Farooq; Feng, Run; Fang, Xingxing; Song, Jiamin; Liang, Yuanyuan; Wu, Zhenzhen; Pan, Shengnan; Tang, Jianping (Frontiers in Pharmacology, 2021)
Objectives: This meta-analysis was conducted to evaluate the effects of hydroxychloroquine (HCQ) in the treatment of primary Sjögren's syndrome (pSS). Methods: Nine databases were searched for data collection. We used clinical features, including involvement in superficial tissues and visceral systems, and experimental findings, including Schirmer’s test, unstimulated salivary flow rate (uSFR), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and immunoglobulins (IgG, IgM and IgA) as major outcome measures. The Downs and Black quality assessment tool and RevMan 5.3 were used to assess the methodological quality and statistical analysis, respectively. Results: Thirteen studies with a total 987 pSS patients, consisting of two randomized controlled studies, four retrospective studies and seven prospective studies were analyzed. Results showed that HCQ treatment significantly improved the oral symptoms of pSS patients compared to non-HCQ treatment (P=0.003). Similar trends favoring HCQ treatment were observed for uSFR (P=0.05), CRP (P=0.0008), ESR (P＜0.00001), IgM (P=0.007) and IgA (P=0.05). However, no significant improvement was observed in other clinical features, including ocular involvement, fatigue, articular lesions, pulmonary, neurological and lymphoproliferative symptoms, renal organs and other experimental parameters in the HCQ treatment group compared to the non-HCQ treatment group. Conclusion: HCQ treatment showed moderate efficacy to improve oral symptoms, uSFR, ESR, CRP, IgM and IgA. However, HCQ could not alleviate organ-specific systemic involvement. To date, a few limited studies have highlighted the efficacy of HCQ for the treatment of pSS. Therefore, well-designed randomized controlled trials are needed to provide more extensive evidence to support these findings.